Girl from the north country [compact disc] : original Broadway cast recording - Dylan, Bob, 1941- (Legacy, 2021)
A full-length musical theater piece, written and directed by Conor McPherson, which boldly reimagines the songs of Bob Dylan in provocative new dramatic contexts. All lyrics and music in the show are by Bob Dylan except for two co-writes. The Original Broadway Cast performing Girl from the North Country includes Todd Almond, Jeannette Bayardelle, Caitlin Houlahan, Robert Joy, Tony Award nominee Marc Kudisch, Luba Mason, Matt McGrath, Jay O. Sanders, and Tony/Academy Award nominee and two-time Emmy Award winner Mare Winningham.